Effect of dextran sulphates on thrombin activity. Issue 5 (May 1979) - Suzuki, K; Hashimoto, S
Abstract : To clarify the action of dextran sulphate, a heparin analogue, in the clotting of fibrinogen by thrombin, determinations were carried out on the clotting activity, the release of fibrinopeptides from fibrinogen, and the hydrolytic activity of thrombin against a peptide chromogenic substrate in the absence or presence of antithrombin III (heparin cofactor). It was shown that dextran sulphate itself inhibited thrombin activity, and its inhibition was dependent on the molecular weight and the sulphur content of the dextran sulphate. Although heparin markedly enhanced the antithrombin activity of antithrombin III, dextran sulphate did not activate antithrombin III.